Factors Contributing to Husbands’ PMO Behavior and Its Impact on Marital Life from the Perspective of Islamic Law - Muhammad Akbar Rauf; Syailendra Sabdo Djati (Asosiasi Dosen Muda Indonesia, 2026)
This study examines the factors contributing to Pornography, Masturbation, and Orgasm (PMO) behavior among husbands, its effects on marital life, and its assessment from the perspective of Islamic law. A descriptive-analytical qualitative approach was employed, with data collected through in-depth semi-structured interviews, non-participant observation, and document analysis involving married men with current or previous PMO experiences and wives as supporting informants. The findings indicate that PMO behavior is driven by several interrelated factors, including early exposure to pornography, psychological stress, sexual dissatisfaction, permissive social environments, and the widespread accessibility of digital technology. These behaviors negatively affect marital relationships by contributing to emotional disconnection, loss of trust, reduced sexual satisfaction, partner betrayal trauma, sexual disengagement, and body image distortion among wives. From the perspective of Islamic law, pornography and associated sexual behaviors are considered contrary to the principles of sexual morality and marital responsibility, while the majority of Islamic jurists regard masturbation as prohibited except under limited circumstances. Such behavior may also undermine the objectives of maqashid al-shariah, particularly the protection of religion (hifzh al-din), intellect (hifzh al-‘aql), and lineage (hifzh al-nasl). The study concludes that addressing PMO behavior among husbands requires a holistic approach that integrates psychological rehabilitation, improved marital communication, spiritual repentance, and sustained religious practices to restore individual well-being and marital harmony.